2019
DOI: 10.1002/ejhf.1540
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital initiation of sacubitril/valsartan in acute decompensated heart failure: being in the right place at the right time

Abstract: This article refers to 'Initiation of sacubitril/valsartan in haemodynamically stabilised heart failure patients in hospital or early after discharge: primary results of the randomised TRANSITION study' by R. Wachter et al., published in this issue on pages 998-1007. < 65 years, SBP ≥ 120 mmHg at baseline, history of hypertension, de novo HF, absence of atrial fibrillation at baseline, an estimated glomerular filtration rate (eGFR) > 60 mL/min/1.73 m 2 at randomization, and a higher starting dose of sacubitril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Despite the inherent limitations of the study [32], TRAN-SITION showed emphatically that soon after hospitalization for AHF, it is feasible to achieve effective doses of sac/val in clinically stable patients within a short timeframe.…”
Section: Sac/val In Ahf a Transition Studymentioning
confidence: 95%
“…Despite the inherent limitations of the study [32], TRAN-SITION showed emphatically that soon after hospitalization for AHF, it is feasible to achieve effective doses of sac/val in clinically stable patients within a short timeframe.…”
Section: Sac/val In Ahf a Transition Studymentioning
confidence: 95%